ENHANCING STUDENT’S ENGLISH VOCABULARY THROUGH FLASHCARDS (AN ACTION RESEARCH AT TK AN-NUUR BEKASI) - Dian Hikmawati; Yon A. E; Syamsi Edi (Samudra Publisher, 2024)
This study is Classroom action research. This study aims to improve students' vocabulary through Flashcards media, especially in class B - 2 AN-Nuur Bekasi Kindergarten. This researcher used the Classroom Action Research (CAR) method which aims to improve students' vocabulary skills. This classroom action research was conducted based on Kemmis and Mc Taggart design. This research consists of two cycles, where each cycle consists of planning, action, observation and reflection. In obtaining data, the author used quantitative and qualitative methods. Qualitative data was obtained through observation and quantitative data was obtained through tests (pre-test and post-test). The results of the two cycles show that the use of flashcards media can improve students' vocabulary mastery. Students experienced an increase in vocabulary addition. In addition, students' achievement in the pre-test and post-test showed significant retention. The average score of students in the pre-test was 49.42 or 14.28% (2 students who passed by obtaining a 3-star score or already declared developing as expected /DAE). The average score on post-test 1 was 61.71 or 28.57% (4 students who passed by obtaining a 3-star rating or already stated as developing as expected /DAE), and the average score on post-test 2 was 82.57 or 85.71% (12 students who passed by obtaining a 3-star rating or already stated as developing as expected /DAE). From these results, the author can conclude that flashcards media for English subjects at AN-Nuur Bekasi Kindergarten can improve students' learning abilities, especially in vocabulary mastery. Thus, the students gain more experience and improve their achievement.